ABC inequalities for some moduli spaces of log-general type - Kim, M (International Press, 1998)
We prove a new bound for the Arakelov-Faltings height of an abelian variety over a function field of characteristic zero and relate it to inequalities of ABC-type as conjectured by Buium and Vojta.